Potencial de aplicação do modelo de sustentabilidade para sistemas agroflorestais proposto por Machado Junior (2019) - Vargas, Jancy Rômulo Aschauer (2022)
Inadequate soil and water management has led to a historic suppression of native forest cover. The process of restoring forests contributes to improving the regulation of water resources and, consequently, sustainability. Agroforestry Systems (SAFs) are one of the main strategies suggested in the literature for environmental recovery, since the characteristics related to their implementation lead to meeting relevant aspects in several dimensions of sustainability (environmental, economic, sociocultural, politicalinstitutional, etc.). In this context, there is a lack of experimentation in SAFs around the design of sustainability assessment models. Therefore, a theoretical model of sustainability proposed by Machado Júnior (2019) was selected, which systematized a list of sustainability indicators for SAFs. This model stands out for contemplating the analysis of significant operating elements and endogenous and exogenous base resources of the system. The model brought a significant methodological-conceptual contribution, however demanding experimental applications that allow the evaluation of its application potential in a broader way. In this sense, in general, the present work sought to examine the potential for application of the model through experimentation with some pilot SAFs. The model was applied in three SAFs located in the state of Espírito Santo – chosen after applying selection criteria. For the experimental application itself, a field protocol was developed and a preliminary experimental application was carried out in a fourth SAF, in order to allow adjustment in the protocol developed herein. From the experimentation of the model proposed by Machado Junior (2019) in the selected SAFs: it was found that the model was sensitive to the variability of environmental, economic, sociocultural and political-institutional factors characteristic of each SAF. And it was possible to highlight the model´s dimensions with greater or lesser tendency towards sustainability. With the experimentation, it was also possible to propose guidelines for the improvement and operationalization of the model. It was concluded that the model has the potential to support the monitoring of SAFs already implemented regarding to its sustainability, and can help in proposing recommendations for the implementation and monitoring of actions, projects and programs of SAFs in support of water resources management.